PERAN IMBALAN PASKA KERJA SEBAGAI PEMODERATOR ATAS PENGARUH PENYUSUTAN ASET TETAP DAN CADANGAN KERUGIAN PIUTANG TERHADAP PENGHASILAN KENA PAJAK. - Muntaha; Djaddang, Syahril (SEKOLAH PASCASARJANA PRESS, 2018)
Principal problems in this research is the influence of depreciation of fixed assets, depreciation of fixed assets moderated by post-employment benefits, allowance for doubtful accounts and allowance for doubtful accounts that are moderated by post-employment benefits on taxable income. This research method uses quantitative approach by using several banking companies listed in Indonesia Stock Exchange period 2011-2015 as research material and take as many as 30 (thirty) population and 12 (twelve) samples to be used as research material. The results of this study indicate a significant effect of Depreciation of Property Assets on Taxable Income, but after the fixed assets Depreciation variable is moderated by Post-Employment Rewards to have no effect on Taxable Income. While the variable Loss of Accounts Receivable does not show any effect on Taxable Income but after moderated by Post-Employment Reward variable it has a significant effect on Taxable Income. PostEmployment Benefits Variables, Depreciation of Fixed Assets and Loss of Receivables are included in the Temporary Different category in the fiscal correction and is one of the causes of the difference between the results of the calculation of Taxable Income between the Directorate General of Taxes and the Taxpayers to determine the Taxable Income for taxpayers .